Alienation of the Set-Valued Drygas-Additive and Quadratic-Additive Functional Equations - Elham Mohammadi; Abbas Najati; Iz-iddine EL-Fassi (Sahand Communications in Mathematical Analysis)
Consider $Y$ as a real Hausdorff topological vector space and $(G,+)$ as a  Abelian group  uniquely divisible by 2. In this paper, the solutions and stability of the Pexiderized set-valued functional equations\begin{align*}    f(x+y)+f(x-y)+g(x+y)&=2f(x)+f(y)+f(-y)+g(x)\\    & \quad +g(y), \\    f(x+y)+f(x-y)+g(x+y)&=2f(x)+2f(y)+g(x)+g(y),\end{align*}are investigated, where $f$ and $g$ are unknown functions  from $G$ to $cc(Y)$.